One or two diffuse-avoidant styles in Berzonsky model? Unresolved problem in the new version of Identity Styles Questionnaire (ISI-4) - Topolewska, Ewa; Cieciuch, Jan (Studia Psychologica: Theoria et praxis, 2012)
In the social-cognitive model of identity formation Berzonsky, (1989, 2011) distinguishes three styles of identity formation: informational, normative and diffuse-avoidant. In order to measure these three styles Berzonsky developed Identity Styles Inventory (ISI). Factorial validity of the questionnaire was usually established via Conhrmatory Factor Analysis with parceling (Crocetti, Rubini, Berzonsky, Meeus, 2009; Crocetti, Shokri, 2010; Zimmermann, Biermann-Mahaim, Mantzouranis, Genoud,Crocetti, 2012). Recently Cieciuch (2010) challenged the results obtained in those analysis and demonstrated that the diffuse-avoidant style should be treated as two-dimensional constructin Poland. In the meantime Berzonsky (2010) developed a revised version of ISI (ISI-4). We address the problem pointed out by Cieciuch (2010) in the Polish data collected with ISI-4. Exploratory and conhrmatory factor analyses, as well an inspection of the association between identity styles and both personality traits and priorities of values strongly support the necessity to split the diffuse-avoidant style measured by ISI4 in Poland into two subtypes